Coastal zone management as land planning - Brower, David J.; Carol, Daniel S.; NPA Joint Committee on Long-Range Land-Use Planning (Washington, D.C.: National Planning Association, 1984)
As a result of the experiences under Coastal management programs (CMPs) by the states' this study will review a number of these experiences, within the general context of evaluating the development of coastal zone management (CZM) as it is practice in the United States.
Includes bibliographical references.
hza 12/07/2018
Loans
Keywords: Coastal zone management; Land use; United States